2017
DOI: 10.15761/adcn.1000104
|View full text |Cite
|
Sign up to set email alerts
|

An evidence-based technological caregiver skill building intervention for dementia family caregivers: pilot study

Abstract: Family caregiving is a growing public health concern and caregivers of persons with Alzheimer's disease or other related dementias (ADRD) need appropriate, timely, and ongoing education and support to successfully meet their caregiving responsibilities. Well-designed interventions can significantly reduce risk concerning caregiver mental and physical health, and improve care recipient outcomes. Few interventions are translated into everyday practice; and most rely on in-person, professionally-led delivery meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Six of them were delivered via telephone or combined face-to-face with telephone-based activities, and one was online. Interventions were focused on managing dementia behavior,24 promoting physical activity,25,26 or combined several activities to improve various outcomes, such as social support, psychological skills, and lifestyle 2729. Six interventions were undertaken in the United States and one in Turkey.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six of them were delivered via telephone or combined face-to-face with telephone-based activities, and one was online. Interventions were focused on managing dementia behavior,24 promoting physical activity,25,26 or combined several activities to improve various outcomes, such as social support, psychological skills, and lifestyle 2729. Six interventions were undertaken in the United States and one in Turkey.…”
Section: Resultsmentioning
confidence: 99%
“…Farran et al27 developed an online version of the “carer skill building” program and tested its benefits with 100 carers. Results showed a significant increase in caring skill at 6 and 12 weeks and improvements in carer depressive symptoms ( P =0.01) and positive affect at 6 weeks ( P =0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Eighty-five papers covering 49 studies were included (some studies were demonstrated in a series of papers). The included studies consisted of 19 RCTs [ [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ], 10 non-RCTs [ [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] ], 4 descriptive quantitative studies [ [57] , [58] , [59] , [60] ], 4 qualitative studies [ [61] , [62] , [63] , [64] ] and 12 mixed-methods studies [ [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] ], see Appendix A . These studies were conducted in America ( n = 25), Netherlands ( n = 4), Canada ( n = 2), France ( n = 1), India ( n = 1), China ( n = 1), Australia ( n = 3), United Kingdom ( n = 2), Spain ( n = 1), Greece ( n = 1), Ireland ( n = 1), Korea ( n = 1), Iran ( n = 1) and multiple European countries ( n = 5).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies pointed out that family caregivers have limited access to dementia-related information. Family caregivers desired more detailed information, such as stage-specific dementia information, attention to more difficult behaviors and complex issues, end-of-life planning and local resource [ 46 , 49 , 67 , 69 , 73 , 74 ]. Five studies perceived that more culturally, ethnically, or gender-related components may influence the delivery of online educational programs [ 28 , 34 , 39 , 54 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation